Identification of a Pathogenic TGFBR2 Variant in a Patient With Loeys–Dietz Syndrome - Luo, Xi; Deng, Shan; Jiang, Ying; Wang, Xiang; Al-raimi, Abdulrahman Mustafa Ahmed; Wu, Long; Liu, Xiaobin; Song, Yu; Chen, Xiao; Zhu, Feng (Frontiers in Genetics, 2020)
Loeys-Dietz syndrome (LDS) is a rare connective tissue genetic disorder that is caused by a pathogenic variant in genes of TGFBR1, TGFBR2, SMAD2, SMAD3, TGFB2 or TGFB3. It is characterized by aggressive vascular pathology, aneurysms, arterial tortuosity, bifid uvula, hypertelorism and cleft palate. Here we present a 42-year-old female patient with LDS. The patient underwent rapidly progressing artery aneurysms and life-threatening aortic dissection. Spontaneous fracture of the first metatarsal bone was noted in her medical record. Physical examination revealed a delayed wound healing on her left abdomen. Considering these clinical manifestations, we speculated that there was a genetic defect in the connective tissue, which provides strength and flexibility to structures such as bones, skins, ligaments, and blood vessels. Thus, whole exome sequencing was performed on the proband and revealed a heterozygous missense pathogenic variant (c.1613T > C/p.Val538Ala) in TGFBR2, which was a de novo variant in the proband as confirmed by the segregation analysis in parental samples. Although this variant was discovered and associated with the phenotype of LDS previously, the pathogenicity of the variant had not been confirmed by cellular functional assay yet. To further validate the effects of the variant in vitro, we assessed the canonical TGF-β signaling pathway in mutant cells. Our results showed that the p.Val538Ala variant significantly decreased TGF-β-induced gene transcription and the phosphorylation of Smad2, which were consistent with other pathogenic variants of TGFBR2. In conclusion, this study demonstrates that p.Val538Ala pathogenic variant in TGFBR2 leads to aberrant TGF-β signaling and LDS in this patient.